Security of transport activities and analysis of the efficiency of personal electric transport through inclusion into the unified transport system of Ukraine (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2025)
Ukraine, cooperating with international projects financed by the World Bank, is actively pursuing a policy aimed at integration into the global economic space. This political course creates economic and political prerequisites that require deepening international ties and increasing trade volumes, which ultimately leads to an increase in the intensity of passenger and cargo flows, which contributes to the development of Ukraine in the transport sector. Ukraine's aspiration to integrate into the global economic space requires ensuring the effective functioning of the unified transport system of the state, clear legal certainty and clarity of legal regulation of the transport sector, especially in terms of ensuring road safety. Along with this, there are currently a number of legal problems, which are discussed in this study. Transport is an intermediate link between the creation of products by the manufacturer and their delivery to the consumer, establishing relations between the manufacturer and various sectors of the economy to establish demand for a particular product, moving cargo and carrying out passenger transportation. The role of the transport system in the context of the economic development of the state can be defined as key. Without the proper development of the transport system in Ukraine, the effective functioning of all types of transport, and the provision of quality transport services, stabilization and positive dynamics in the economy are impossible.Keywords: transport safety, efficiency, electric transport, unified transport system of Ukraine